2018
DOI: 10.1016/j.pss.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Meteor showers from active asteroids and dormant comets in near-Earth space: A review

Abstract: Small bodies in the solar system are conventionally classified into asteroids and comets. However, it is recently found that a small number of objects can exhibit properties of both asteroids and comets. Some are more consistent with asteroids despite episodic ejections and are labeled as "active asteroids", while some might be aging comets with depleting volatiles. Ejecta produced by active asteroids and/or dormant comets are potentially detectable as meteor showers at the Earth if they are in Earth-crossing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Our paper is similar to recent similar studies of the relationship between various meteoroid streams and their parent bodies, i.e., cometary (Hajdukova et al 2015;Ishiguro et al 2015;Kornoš et al 2015;Rudawska et al 2016;Abedin et al 2015Abedin et al , 2017Abedin et al , 2018Babadzhanov et al 2017;Jenniskens et al 2017;Šegon et al 2017) and lately also asteroidal (Babadzhanov et al 2015a,b;Jopek 2015;Jopek & Williams 2015;Rudawska & Vaubaillon 2015;Olech et al 2016;Wiegert et al 2017;Dumitru et al 2018;Sergienko et al 2018a,b;Ye 2018;Guennoun et al 2019;Ryabova et al 2019). Some authors have attempted to work out or improve a method of prediction of particular shower, often on the basis of known parent body (Koten & Vaubaillon 2015;Ryabova 2016;Sugar et al 2017;Vaubaillon 2017;Ryabova & Rendtel 2018a,b).…”
Section: Introductionsupporting
confidence: 91%
“…Our paper is similar to recent similar studies of the relationship between various meteoroid streams and their parent bodies, i.e., cometary (Hajdukova et al 2015;Ishiguro et al 2015;Kornoš et al 2015;Rudawska et al 2016;Abedin et al 2015Abedin et al , 2017Abedin et al , 2018Babadzhanov et al 2017;Jenniskens et al 2017;Šegon et al 2017) and lately also asteroidal (Babadzhanov et al 2015a,b;Jopek 2015;Jopek & Williams 2015;Rudawska & Vaubaillon 2015;Olech et al 2016;Wiegert et al 2017;Dumitru et al 2018;Sergienko et al 2018a,b;Ye 2018;Guennoun et al 2019;Ryabova et al 2019). Some authors have attempted to work out or improve a method of prediction of particular shower, often on the basis of known parent body (Koten & Vaubaillon 2015;Ryabova 2016;Sugar et al 2017;Vaubaillon 2017;Ryabova & Rendtel 2018a,b).…”
Section: Introductionsupporting
confidence: 91%
“…1), the lunar impact record and its crater size-frequency distribution are commonly used as a proxy for the impact crater production rate on Earth (e.g., Neukum and Ivanov, 1994;Neukum et al, 2001;Werner et al, 2002;Ivanov et al, 2003). Additional constraints come from the size-frequency distribution of near-Earth asteroids (e.g., Shoemaker et al, 1979;Durda et al, 1998;Morbidelli, 1999;Bottke et al, 2000;Werner et al, 2002;Stuart and Binzel, 2004;Michel and Morbidelli, 2007;Le Feuvre and Wieczorek, 2011;Johnson and Bowling, 2014;Wheeler and Mathias, 2019), the population of Earth-crossing comets, the Sun's position in the galactic plane (e.g., Shoemaker, 1998b;Ye, 2018), as well as the distribution of extraterrestrial 3 He (Farley, 1995(Farley, , 1998(Farley, , 2001), platinum-group metals (Peucker-Ehrenbrink, 2001), and fossil meteorites and extraterrestrial chromite grains (e.g., Schmitz et al, 1996Schmitz et al, , 2001Schmitz et al, , 2015Heck et al, 2004;Alwmark and Schmitz, 2009;Schmitz, 2013) in marine sediments. While some authors proposed that the impact flux in the Earth-Moon system has continuously declined over the past 3 Gyr (Minton and Malhotra, 2010), others suggested that the impact flux has remained more or less stable over the last 2 Gyr (e.g., Neukum and Ivanov, 1994;Hörz, 2000;Hughes, 2000).…”
Section: Considerations On the Terrestrial Impact Flux From The Age Dmentioning
confidence: 99%
“…Denning 1893;Plavec 1950;Whipple 1983;Jones et al 2016;Hui & Li 2017;Ryabova & Rendtel 2018, and many others). However, most of the Sun-approaching streams are weakly active and have not received a lot of attention (Ye 2018). Many of these streams do not have identifiable parents, raising questions about their formation mechanism.…”
Section: Introductionmentioning
confidence: 99%